Healthy enough to work up to age 67 and beyond? A longitudinal population-based study on time trends in working life expectancy free of cardiovascular diseases based on German health insurance data - Fabian Tetzlaff; Jelena Epping; Juliane Tetzlaff; Lieselotte Mond (BMJ Public Health)
Background Due to the rising life expectancy in Western countries, the discussion about the increase in the retirement age is becoming more important. However, the prolongation of working lives cannot be implemented successfully without considering the health status of the (potential) employees. In this study, time trends in working life expectancy (WLE) free of widespread cardiovascular diseases (CVD) as well as the proportion of CVD-free working life years are reported.Methods Claims data from a German statutory health insurance provider is used to analyse CVD-free WLE. Three periods were defined to assess time trends: 2006–2008 (n=2 075 248), 2011–2013 (n=2 302 127) and 2016–2018 (n=2 579 985). Based on transition rates between the states labour force, non-labour force, CVD and death, CVD-free years spent in the labour force were estimated for each age using multistate life table analyses.Results The length of CVD-free WLE increased over time. This increase was stronger in women than in men (+6.4 years vs +2.4 years at age 18). Given the increase in total WLE of the study population, the proportion of CVD-free WLE in total WLE remained stable over time.Conclusions The results show that working life years free of CVD increased strongly over the last 13 years and can keep pace with the increase in the length of working lives. Healthier working conditions as well as more efforts in promoting healthy nutrition and less sedentary behaviour could help to further reduce the incidence of CVD and thus contribute to longer healthy working lives.